Influence of Microscopic Parameters on the Stress-Strain Relation in Rocks - Yanhui Cheng; Weijun Yang (Advances in Civil Engineering)
Macromaterial properties should correspond to the mesoscopic parameters simulated in practical engineering problems. Discrete element contains a variety of particle models and its corresponding mesoscopic parameters, and the one-to-one relationship between the mesoscopic parameters and macroscopic parameters is difficult to establish. This paper studies the influence of microscopical characteristic parameters, such as particle contact stiffness ratio, parallel bond stiffness ratio, particle contact modulus, and parallel bond elastic modulus, on the stress-strain relation in rocks, which shows that (1) The range of particle contact stiffness ratio kn/ks largely varies, but the stress-strain relation curve is relatively small. The particle contact stiffness has less influence on the elastic modulus of the simulated specimens than kn/ks. (2) Before the failure of the specimen, the axial strain corresponding to the peak compressive strength increases with the increase in the stiffness ratio kn¯/ks¯ of the parallel bond. (3) The particle contact modulus Ec has a great influence on the elastic modulus of sandstone and is characterized by the increase in the particle contact modulus Ec, corresponding axial strain for the peak compressive strength decreases, and the slope of the stress-strain relationship curves before damage increases. (4) The elastic modulus of the parallel bond greatly influences the uniaxial compressive strength, and the relationship between them is proportional.